Analysis of challenges and opportunities in the development of new energy vehicle battery industry from the perspective of patents. Issue 3 (January 2021) - Tan, Xiumei; Li, Tianyu
Abstract: Thanks to China's "three verticals and three horizontals" strategy and the important deployment of new energy policies, the new energy vehicle industry has developed rapidly. The rapid development has also led to some problems. From a macro point of use, patent is an important index to reflect the technological innovation of the industry, which can provide reference for the long-term development of the industry. From the microcosmic point of office, patent is the embodiment of the strength of research and development and core competitiveness of an enterprise, and is the weather vane of its innovation layout. Therefore, this paper will use patent analysis method, collect domestic 2002-2019 new energy vehicle patent data, analyze the current situation of china's new energy vehicle industry technology innovation from China's new energy vehicle patent application number, patent application trend, patent technology features, patent application geographical distribution, patent application body and other dimensions, comprehend the automotive industry in the face of new challenges and opportunities in the process of new energy vehicle transformation, and provide some ideas for the development of China's new energy vehicle industry on the basis of analysis of relevant issues.